J. I. Packer’s Theology of Justification—His Reception and Appropriation of a Classic Protestant Doctrine - Corneliu C. Simuț (Religions, 2023)
This article is a systematic overview of Packer’s theology of justification from the perspective of descriptive, analytical, and critical methodologies. A series of books written by Packer were investigated in order to identify various references to justification, which led to a categorization consisting of six features (justification as the legacy of the Reformation, eternal status, a precursor of sanctification, trust in Christ, covenant reality, and a divine promise). Two of Packer’s most important books used for this research, Keep in Step with the Spirit: Finding Fullness in Our Walk with God (2005) and Concise Theology: a Guide to Historic Christian Beliefs (2011), also revealed the theological foundation of justification, which I present as the two pillars on which Packer’s theology of justification stands: God’s being and Christ’s incarnation. These two pillars reveal not only God’s invisible being as Trinity but also his self-disclosure in Christ as an exclusive focus of the sinners’ belief of justification. The six features and the two pillars of Packer’s theology of justification demonstrate not only how he received and appropriated the classical Protestant teaching about God’s decision to consider sinners righteous despite their sins but also how it generates, through faith in Christ, a consistently new life.